Resolving conflicts at work : ten strategies for everyone on the job - Cloke, Ken.; Goldsmith, Joan. (San Francisco : Jossey-Bass, 2011)
"The classic text on resolving workplace conflicts, fully revised and updated Resolving Conflicts at Work is a guide for preventing and resolving conflicts, miscommunications, and misunderstandings at work, including dozens of techniques for revealing how the inevitable disputes and divisions in the workplace are actually opportunities for greater creativity, productivity, enhanced morale, and personal growth. In the third edition of this text, all chapters are completely infused with additional content, updated examples, and new case studies. Like its predecessors, it identifies core strategies for preventing and resolving both intermittent and chronic conflicts in the workplace.?In addition, the book Includes a new foreword by Warren Bennis, which represents his most recent thinking about judgment calls and candid communications in the workplace Presents new chapters on leadership and transformational conflict coaching, and organizational systems design Features downloadable teaching materials available for faculty using the book This definitive and comprehensive work provides a handy guide for managers, employees, union representatives, human resource experts, and consultants seeking to maintain stable and productive workplaces"--
Includes bibliographical references and index.
Keywords: Conflict management; Interpersonal relations; Personnel management -- Psychological aspects; Psychology, Industrial